Scientists dealing with stakeholders' demand for coral reef management indicators: methodological approach and issues. (6th July 2007) - Antona, Martine; David, Gilbert; Mirault, Emilie
The purpose of this paper is to analyse how to relate scientific supply to demand regarding sustainable management indicators. This discussion is based on coastal zone management in Reunion Island, for which socioeconomic indicators have been developed. This research allows us to establish conditions to connect social demand with the scientific supply of indicators: to develop an iterative process, which associates stakeholders, for identifying and selecting indicators; to strengthen the coherence between demand and supply of indicators: this should be achieved through better connections between the representations developed by stakeholders and scientists of the system to be managed; to consider the issue of environmental decision making and responsibility. Environmental research must focus on the design of the process of selection of relevant indicators. This research must also assess and monitor the use of indicators for the decision-making process. This involves the development of methodologies enabling this co-elaboration between users and scientists, while considering areas of public policy action and assessment.